Innovation systems and technical efficiency in developing-country agriculture - Mekonnen, Dawit Kelemework; Spielman, David J.; Fonsah, Esendugue G.; Dorfman, Jeffrey H. (Wiley, 2015)
This article examines how different components of an agricultural innovation system interact to determine levels of technical inefficiency in developing‐country agriculture. The analysis draws on data from 85 low‐ and middle‐income countries for the period 2004–2011 to estimate latent class stochastic frontiers in which the technological class to which the country belongs is determined within the model. To enable efficiency comparisons between countries across these technological classes, we estimate a meta‐frontier that encompasses all the class frontiers. We embed components of an agricultural innovation systems framework in this estimation to explain countries’ technical inefficiency with respect to their respective class frontiers. Mobile phone subscriptions as a measure of institutions that facilitate the transfer of knowledge and information as well as the number of scientific and technical journal articles as a measure of research productivity and knowledge production are found to improve technical efficiency of agricultural production in these countries. The mean technical efficiency score of agricultural production between 2004 and 2011 for countries in class one is 44.1% whereas it is 62.7% for countries in class two, indicating sizeable potential to improve agricultural production from the same level of agricultural inputs through efficiency‐enhancing investments.